Advancing pet care through technology: An evaluation of the LINE-based VET PROMPT notification system - Somrup, Supaporn; Sirimalaisuwan, Anucha; Chaisowwong, Warangkhana; Na Lampang, Kannika (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study evaluated the effectiveness of the VET PROMPT notification, accessed via the LINE Application Official Account (LAOA). Materials and Methods: In enhancing communication between veterinarians and pet owners. By leveraging pets online, it offers a convenient and cost-effective solution for pet owners to receive timely and pertinent veterinary information, appointment notifications, and disease prevention guidance for their pets. The research involved administering a satisfaction questionnaire to pet owners who subscribed to the LAOA–VET PROMPT group and analyzing responses using statistical measures such as percentage, mean, standard deviation, and one-way ANOVA. Results: Findings revealed high levels of satisfaction among users, particularly with the system’s responsiveness and the completeness and accessibility of online pet healthcare. Furthermore, the study discovered significant variations in satisfaction levels based on the type of pet owned, indicating that the specific needs and preferences of different pet owner groups uniquely influence their satisfaction with the VET PROMPT. Conclusion: Overall, the integration of automatic notifications into pet owners’ mobile devices significantly enhanced the management and care of pets through streamlined communication. J. Adv. Vet. Anim. Res., 12(3): 849–860, September 2025 http://doi.org/10.5455/javar.2025.l947